Analisis Yuridis Tanggung Jawab Tenaga Kesehatan Terhadap Pengesampingan Hak Peserta Jaminan Kesehatan Nasional Ditinjau Berdasarkan Hukum Positif Indonesia - Felen Felen (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In line with the concept of a welfare state, Indonesia, as a country, is obligated to implement and ensure the welfare of its citizens, including in the national healthcare sector. To ensure the inclusivity of national health coverage, the government, through the BPJS Kesehatan agency, has established the National Health Insurance (JKN) program, which is mandatory for all citizens, as stipulated in Indonesian legislation. However, the effort to achieve inclusivity may become biased if there is no clear regulation regarding the rights of participants and the obligations of healthcare providers, who play a crucial role in this process. Under Indonesian positive law, the rights of JKN participants are thoroughly regulated, as are the obligations of healthcare providers. However, based on observed phenomena, there are still violations of these obligations by healthcare providers, leading to the neglect of participants' rights. This research aims to raise awareness among stakeholders and provide a foundation for future research. The type of research used in this paper is normative legal research, which focuses on the analysis of legal norms.